Otimização da microestrutura de componentes de pilhas a combustível de óxido sólido a temperaturas intermediárias - Jacqueline Amanda Figueiredo dos Santos (2014)
The solid oxide fuel cells are devices capable of converting chemical energy into electrical energy in a highly efficient manner and with low waste generation. Therefore they are likely to be one of the major energy devices in the future. However, for widespread use ofthe same, many studies are still needed in order to obtain good performances even at intermediate temperatures (600-800 °C), which would favor the price reduction and the extended life of these devices. For this reason, it becomes necessary to develop the constituents of this cell, regarding composition and morphology of these materials. In thisstudy, it is developed the functional cathode and the cathode collector (constituted by lanthanum strontium cobalt iron oxide) as well as one of the SOFC electrolytes (consisting of gadolinium doped ceria). The main objective was to develop the microstructure of these components; since the electrolyte should be dense while cathode collector should be porousand functional cathode must have intermediate porosity relative to adjacent layers. To achieve this microstructure, several variables in the production of ceramic materials were evaluated, such as particle size of powders, use of doping for favoring gadolinium doped ceria densification, viscosity of ceramic suspensions, use of pore-forming, the film deposition technique (screen printing or spray coating), parameters of the films deposition (such as speed, pressure, number of layers, mesh screen), type of heat treatment used, etc. Besides the morphological aspect, the electrochemical behavior was also evaluated, since it wishedto obtain materials that were good electrical conductors. The influence of the powder composition, doping, use of additives and sintering temperature on the conductivity of these materials was evaluated. The results show it is possible to obtain a dense gadolinium dopedceria electrolyte by spray when using doping with zinc and a sintering temperature of 1500 °C. Regarding the cathode collector, the graphite pore former made possible to obtain a porous structure and good conductivity with the use of composition La0,6Sr0,4Co0,8Fe0,2O3-,On the other hand, functional cathode proved to be effective when prepared in form of the composite La0,54Sr0,44Co0,2Fe0,8O3/ Gd0,2Ce0,8O2-d., and sintered at temperatures higher thanthe cathode collector.